2008
DOI: 10.5194/bg-5-937-2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV radiation and temperature on the emission of methane from plant biomass and structural components

Abstract: Abstract.The recently reported finding that plant matter and living plants produce significant amounts of the important greenhouse gas methane under aerobic conditions has led to an intense scientific and public controversy. Whereas some studies question the up-scaling method that was used to estimate the global source strength, others have suggested that experimental artifacts could have caused the reported signals, and two studies, one based on isotope labeling, have recently reported the absence of CH 4 emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
232
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(273 citation statements)
references
References 24 publications
(38 reference statements)
23
232
4
Order By: Relevance
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…soil or plant water) and whether plants have their own mechanism(s) to produce CH 4 have been debated (Bruhn et al, 2012;Keppler et al, 2009;Nisbet et al, 2009). Evidence is now accumulating to indicate that plants can produce CH 4 even in the presence of oxygen (Bruggemann et al, 2009;Bruhn et al, 2009Bruhn et al, , 2014Cao et al, 2008;Fraser et al, 2015;Keppler et al, 2008;Lenhart et al, 2014;McLeod et al, 2008;Messenger et al, 2009;Mikkelsen et al, 2011;Reid, 2009, 2011;Sanhueza and Donoso, 2006;Sinha et al, 2007;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2009aWang et al, , 2009bWang et al, , 2011aWatanabe et al, 2012;Wishkerman et al, 2011).…”
Section: Plantsmentioning
confidence: 99%
“…The impacts of UV radiation and heating on CH 4 emissions from detached leaves (Bruhn et al, 2009;Fraser et al, 2015;McLeod et al, 2008;Reid, 2009, 2011;Vigano et al, 2009Vigano et al, , 2008Wang et al, 2011b), intact plants and structural components (e.g. pectin, lignin, cellulose and leaf surface wax) (Bruhn et al, 2014;Keppler et al, 2008;McLeod et al, 2008;Messenger et al, 2009;Vigano et al, 2009Vigano et al, , 2008 have been extensively tested.…”
Section: Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that CH 4 can be produced abiotically from plant material by exposing it to ultraviolet (UV) irradiation [15][16][17][18] . A reaction of reactive oxygen species (ROS) with methoxyl groups of pectic polysaccharides was suggested as a possible route to CH 4 formation under UV radiation 19 .…”
mentioning
confidence: 99%